¿Discapacidad? : literatura, teatro y cine hispánicos vistos desde los disability studies - Checa, Julio; Hartwig, Susanne (Images of disability, 2018)
"Functional diversity, understood as a bodily, cognitive or psychic affection, often seriously disrupts the participation of people in collective life. At times, functional diversity can also be accompanied by a strong social stigma. This volume offers one of the first approaches to the representation of functional diversity in the Hispanic sphere. The works included in this book are in charge of showing the possible theoretical and practical approaches to the representation of functional diversity, through a varied corpus composed of literary, scenic, cinematographic and audiovisual works, extracted from the contemporary Hispanic creation"--Publisher's website.